Análise da concordância entre instrumentos de avaliação de flexibilidade para os músculos isquiocrurais em idosos - Tozim, Beatriz Mendes [UNESP]; Lorenzo, Daniele Moraes de [UNESP]; Furlanetto, Mariana Giglio [UNESP]; Morcelli, Mary Hellen [UNESP]; Navega, Marcelo Tavella [UNESP] (My University, 2014)
Introduction : The aging is characterized by a reduction in the effectiveness of skills, among them the loss of the flexibility. The hamstring muscles may be affected by the decreased flexibility occurs when elderly can present limitation of gait, low back problems and osteomuscular. Among the techniques used to evaluate the flexibility of the hamstring muscles are the Sit and Reach Test and Computerized Photogrammetry evaluation of the popliteal angle . However, the scientific literature doesn’t provide consistent data on the correlation of these forms of evaluation. Objective: To analyze the correlation between the sit and reach test and Computerized Photogrammetry evaluation of the popliteal angle used to assess the flexibility of the hamstring muscles in elderly women. Method: This was a cross-sectional, observational study, consisting of 39 elderly, healthy. The evaluation was composed by forms with personal details and physical examination (body weight, height and body mass index), and the evaluation of tests to measure the flexibility of the hamstring muscles (Sit and reach test and Computerized Photogrammetry evaluation of the popliteal angle). The correlation of the data was done by using the Spearmam’s rank correlation coefficient, with a significance level of 5% (p<0.05). Results: The data showed a positive correlation between Sit and Reach Test Computerized Photogrammetry and the popliteal angle of the right leg (r=0.4690, p=0.0026) and the left leg (r=0.3604, p=0.0241). Conclusion: The data from this study allow conclude that the tests for assessing hamstring flexibility in elderly women, the Sit and Reach Test and Computerized Photogrammetry evaluation of the popliteal angle are complementary because it doesn’t correlate strongly.

Introdução: O envelhecimento é caracterizado pela redução na eficácia das habilidades, dentre elas esta a perda de flexibilidade. Os músculos isquiocrurais podem ser acometidos pela diminuição da flexibilidade quando ocorre os idosos podem apresentar limitação da marcha, problemas lombares e osteomusculares. Dentre as técnicas utilizadas para avaliar a flexibilidade dos músculos isquiocrurais esta o Teste Sentar e Alcançar e a Fotogrametria Computadorizada da avaliação do ângulo poplíteo. Entretanto, a literatura científica não apresenta dados consistentes sobre a concordância dessas formas de avaliação. Objetivo: Analisar a correlação entre o Teste sentar e alcançar e a Fotogrametria Computadorizada da avaliação do ângulo poplíteo usados para avaliar a flexibilidade dos músculos isquiocrurais em idosas. Método: Tratou-se de um estudo transversal, observacional, formado por 39 idosas, hígidas. A avaliação foi composta por ficha com dados pessoais e exame físico (Massa corpórea, estatura e índice de massa corpórea), além de ser realizada a avaliação dos testes para medir a flexibilidade dos músculos isquiocrurais (Teste Sentar e alcançar e Fotogrametria Computadorizada da avaliação do ângulo poplíteo). A correlação dos dados foi feita por meio da aplicação do Coeficiente de Correlação de Spearman, com nível de significância de 5% (p<0,05). Resultados: Os dados mostraram correlação positiva entre o Teste Sentar e Alcançar e a Fotogrametria Computadorizada do ângulo poplíteo do membro inferior direito (r=0,4690; p=0,0026) e do membro inferior esquerdo (r= 0,3604, p=0,0241). Conclusão: Os dados do presente estudo permitem concluir que os testes para avaliação de flexibilidade isquiocrurais em idosas, o Teste Sentar e Alcançar e a Fotogrametria Computadorizada da avaliação do ângulo poplíteo são complementares, pois não se correlacionaram fortemente.
Analysis of agreement between assessment tools for hamstring flexibility in elderly.